PERBANDINGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DAN PROJECT BASED LEARNING (PjBL)TERHADAP HASIL BELAJAR DAN MOTIVASI PESERTA DIDIK PADA MATERI VIRUS KELAS X MAN 1 ROKAN HULU - Nadia Oktaviani Lorenza; Rena Lestari; Jismi Mubarrak; Dahlia Dahlia; Eti Meirina Brahmana; Arief Anthonius Purnama; Ria Karno; Sri Wahyuni (Jurnal Edu Research, 2025)
This research aims to determine the Comparison of PBL and PjBL Learning Models on learning outcomes and student learning motivation in the class X virus meteri MAN 1 Rokan hulu TP 2023/2024. Population The study population is all class X students at MAN 1 Rokan Hulu TP 2023/2024 as many as 4 classes with a total of 74 students. Sample taken randomly as many as 2 classes, namely class X3 as a class taught using the Problem Based Learning (PBL) model. using the Problem Based Learning (PBL) model and X2 as a class that is taught using the Projet Based Learning model. which is taught using the Projet Based Learning (PjBL) model, totaling 17 and 19 students respectively. totaling 17 and 19 students. So that the number of samples in this study 36 students. The type of research conducted is Quasi Experiment. The results of the study showed that there was no significant comparison between the application of PBL and PjBL models model on learning outcomes and student learning motivation in virus material class X MAN 1 Rokan Hulu. Both models are equally effective in improving learning outcomes and student motivation.